Analisis Kinerja Keuangan Perusahaan Sub Sektor Asuransi yang Terdaftar di Bursa Efek Indonesia Sebelum dan Sesudah Pandemi Covid 19 - Intan Febrianingsih; Salma Taqwa (Universitas Negeri Padang, 2024)
This research purposes to analyze the performances analysis of insurance sub-sector company listed on Indonesia Stock Exchange Before and After Covid-19. The researcher applied descriptive research. This research population was insurance sub-sector companies registered on IDX in 2018–2021. Sampling technique of this research was purposive samping. It consisted of 14 companies. type of data was secondary data acquired from IDX website and website of each company. This result showed that 1) there was no significant difference in financial performances in term of liquidity indicators before and after Covid-19, 2) there was no significant difference in financial performances in the term of activity indicators before and after Covid-19, 3) there was no difference significant financial performances described from solvency indicators before and after Covid-19, 4) there was no significant difference financial performances described from profitability indicators before and after Covid-19.